Social and economic well-being in the conditions of the urban space: the evolution of methodological approaches in the historical urban studies; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Ageev I. A. Iliya Aleksandrovich (2016, 2016)
Title screen